Compensatory Genetic and Transcriptional Cytonuclear Coordination in Allopolyploid Lager Yeast (Saccharomyces pastorianus). (19th October 2022) - Zhang, Keren; Li, Juzuo; Li, Guo; Zhao, Yue; Dong, Yuefan; Zhang, Ying; Sun, Wenqing; Wang, Junsheng; Yao, Jinyang; Ma, Yiqiao; Wang, Hongyan; Zhang, Zhibin; et al.
Abstract: Cytonuclear coordination between biparental-nuclear genomes and uniparental-cytoplasmic organellar genomes in plants is often resolved by genetic and transcriptional cytonuclear responses. Whether this mechanism also acts in allopolyploid members of other kingdoms is not clear. Additionally, cytonuclear coordination of interleaved allopolyploid cells/individuals within the same population is underexplored. The yeast Saccharomyces pastorianus provides the opportunity to explore cytonuclear coevolution during different growth stages and from novel dimensions. Using S. pastorianus cells from multiple growth stages in the same environment, we show that nuclear mitochondria-targeted genes have undergone both asymmetric gene conversion and growth stage-specific biased expression favoring genes from the mitochondrial genome donor ( Saccharomyces eubayanus ). Our results suggest that cytonuclear coordination in allopolyploid lager yeast species entails an orchestrated and compensatory genetic and transcriptional evolutionary regulatory shift. The common as well as unique properties of cytonuclear coordination underlying allopolyploidy between unicellular yeasts and higher plants offers novel insights into mechanisms of cytonuclear evolution associated with allopolyploid speciation.